Ocular findings in two Chinese children with Loeys-Dietz syndrome. Issue 6 (November 2022) - Wang, Wenting; Man, Hui; Zhang, Jie; Yu, Penglin; Li, Shuchan; Xu, Xinyan; Li, Nan
Background: Loeys-Dietz syndrome (LDS) is a type of connective tissue disease with systemic symptoms similar to Marfan syndrome. Ocular findings are rarely reported especially fundus and extraocular muscles. Case presentation: A 6-month old boy with systemic skeletal development delay was found peripheral non-perfusion and neovascularization in the both eyes, and gaven intravitreal injection of ranibizumab and laser. Fundus examination revealed a mild straightening of the temporal vessel in the both eyes. A 22-month old girl with confirmed connective tissue disorder presented to our hospital for strabismus and showed congenital hypoplasia of extraocular muscles. She also had arteriovenous anastomosis in the retinal. The diagnosis of LDS was supported by the genetic DNA examination. Conclusion: His is the first report of LDS with congenital hypoplasia of extraocular muscles, meanwhile, ocular examination especially fundus should be paid attention to.